Microwave holographic imaging technique for tumour detection - Maniam, Jayanthy *; Narainasamy, Selvanathan; Abu-Bakar, M.; Smith, D.; Elgabroun, H. M.; Yeong, P. M.; Kumar, S. Senthil (Springer, 2007)
Early, accurate and efficient screening of tumour will go a long way to improve the life expectancy and quality of life. Microwave holographic technique uses nonionising radiation which has the potential to screen patients for tumour at low cost. It offers high contrast between healthy and malignant tissues and assists in forming image of the location and the extent of the malignant tissue. This technique exploits the advantages of holography without requiring the direct measurement which uses an expensive network analyser. This paper will investigate the use of an alternative microwave imaging technique using indirect holographic method. The use of continuous wave signal for imaging avoids the problems associated with pulsed systems. The use of two stage holographic technique requires recording of a holographic interference pattern as stage one and reconstruction of original image of the object as stage two. As a preliminary study, the transmitted microwave signal is bombarded on a suitable phantom and the scattered signals are measured. The significance of this technique is that it offers real time imaging possibility which can be used as intra operative imaging tool during the surgery to remove tumour